Perancangan Sistem Informasi Penjualan Tanaman Hias pada JA Garden (Yayasan Kawanad, 2023)
This research aims to design a web-based information system for selling ornamental plants at JA Garden. This system consists of input, output, process, control, labor, and cost design stages. Each stage is detailed with the programs involved, including data entry programs for categories, products, buyer information, purchase transactions, sliders, brands, blogs, users, and messages. System output includes category recaps, products, customers, transaction reports, transaction details, goods transactions, brands list, sliders, blogs/news, and users. The sales data processing process adopts computerized applications with context, tiered and data flow diagrams. User control involves registration in the database to prevent redundant data. Application control includes user management and data security with encryption. Minimal labor required, with training for application use. The proposed costs cover system maintenance and development. The use of various web programming languages and supporting software such as XAMPP, NotePad++, and the Google Chrome browser supports the functions of this system. Suggestions involve optimizing computer use, improving human resource skills, and utilizing all software. This research is expected to provide guidance for the development and implementation of an ornamental plant sales information system at JA Garden.